2002
DOI: 10.1200/jco.2002.20.5.1304
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognostic Significance of Complete Axillary Downstaging After Primary Chemotherapy in Breast Cancer Patients With T1 to T3 Tumors and Cytologically Proven Axillary Metastatic Lymph Nodes

Abstract: Our results suggest that axillary status is a better prognostic factor than response of the primary tumor to primary chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
134
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(149 citation statements)
references
References 30 publications
8
134
1
6
Order By: Relevance
“…Based on the results of other studies, however, we think it is very likely that there were such patients, and, had they been counted in the pCR group, the rate of pCR would have been higher. Nonetheless, our findings are similar to reports from other trials, where high clinical response rates were seen but pCR rates were disappointing [15][16][17][18][19][20][21]. This trial was designed over twenty years ago, and it is possible that newer regimes are more effective.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on the results of other studies, however, we think it is very likely that there were such patients, and, had they been counted in the pCR group, the rate of pCR would have been higher. Nonetheless, our findings are similar to reports from other trials, where high clinical response rates were seen but pCR rates were disappointing [15][16][17][18][19][20][21]. This trial was designed over twenty years ago, and it is possible that newer regimes are more effective.…”
Section: Discussionsupporting
confidence: 80%
“…In-breast responses can increase the rate of breast conservation and possibly provide prognostic information. In this study, worse overall survival was associated with poor baseline performance status and higher number of involved nodes at surgery, paralleling results of other reports [18,21,[26][27][28]. However, in distinction to other recent reports, clinical response to neoadjuvant doxorubicin did not predict long-term survival.…”
Section: Discussionsupporting
confidence: 73%
“…We noted a very high rate of axillary pCR (95%). As axillary pCR is considered to be a very strong prognostic factor, our findings further emphasize the importance of incorporating trastuzumab into neo-adjuvant treatment in HER2 over-expressing breast cancer patients [5,6].…”
Section: Discussionmentioning
confidence: 75%
“…Thus, pathological complete response (pCR), which can be achieved in up to 35% of the patients treated by anthracycline or taxane based pre-operative therapy, is associated with improved survival [3Á5]. Complete pathological response in the axillary lymph nodes has also been demonstrated to be an independent predictor of long-term outcome, regardless of the response in the breast tissue [5,6].…”
mentioning
confidence: 99%
“…Nearly all neoadjuvant chemotherapy trials demonstrated that survival was correlated with the response to neoadjuvant chemotherapy with survival rates ranging from 85% to 90% for patients with complete breast tumor and lymph node response. 3,33,34 Conversely, patients with no response displayed poor survival. It could be hypothesized that with the regimens of chemotherapy used in the historical randomized trials, two populations can be individualized, namely, one population best treated with preoperative chemotherapy and one best treated with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%